Математическая модель кинематики и динамики винтовой планетарной клети - Жукова, Н. В. (Видавництво Львівської політехніки, 2011)
The mathematical model of the spiral planet breakdown stand, as a planetary differential mechanism with two degrees of freedom. Model satisfies the two criteria of spiral rolling. The results of simulation confirm that the spiral planetary rolling is realized when the forward movement of the metal without its rotation.
Keywords: spiral planet stand; differential mechanism; criteria of spiral rolling; detail; link; closed kinematic chain